A functionalized bio-based material with abundant mesopores and catechol groups for efficient removal of boron. (January 2021) - Xia, Nan Nan; Zhang, Hui Ya; Hu, Zi Hao; Kong, Fangong; He, Fei
Abstract: Pursuing a low-cost yet sustainable material with a high performance of removing boron is necessary for replacement of the synthetic adsorbents, but remains challengeable. Herein, we fabricated an mesopore-dominated bio-based material (LS-CPAM-TA) with abundant catechol groups by the electrostatic-interaction-driven self-assembly of lignosulfonate (LS), tannic acid (TA) and cationic polyacrylamide (CPAM) for efficient removal of boron. LS-CPAM-TA presented a mesopore area of 53.9 m 2 /g with a mesoporous distribution of 2–25 nm, as well as a mesopore/micropore volume ratio of 129.7. Such a mesopore-rich feature not only promoted the exposure of catechol groups in TA, which served as the adsorption sites, but also contributed to enhance the fast mass transport of boron. Consequently, a maximum adsorption capacity of 119.05 mg/g was observed for LS-CPAM-TA, surpassing some reported adsorbents. Even for the low concentration boron, LS-CPAM-TA also displayd the high adsorption efficiency. Moreover, LS-CPAM-TA followed the Langmuir isotherm adsorption model, and presented the excellent regeneration performance due to its robust self-assembled structure driven by the electrostatic interaction among LS, CPAM and TA. This work would provide guidelines for target design of bio-based materials with tunable porous structure and versatile adsorption or catalytic sites for various applications. Graphical abstract: Image 1 Highlights: The mesopore-dominated bio-based adsorbent was constructed by the electrostatic interaction. The bio-based adsorbent contained enriched catechol groups. The bio-based material displayed a high adsorption capacity of boron. The robust supramolecular self-assembled structure enabled the excellent regeneration performance.